Practice on Designing Stages of Work Creation Methods as a Basis for Creating Photographic Works. - Silviana Amanda Tahalea; Erlina Novianty; Pongky Purnama; Ariani Ariani (Altifani Journal: International Journal of Community Engagement, 2024)
Photography, as a combination of art and technology, represents the evolution of the field of fine arts in general, which is interdependent. The scientific aspect of the method of creating photographic works lies in its logical explanation, including the narrative structure and intrinsic qualities of the photographic results. This activity uses several methods, such as counseling or outreach methods, by providing material on creating photographic works for beginners and professional photographers and practicing creating photographic works for around 40 participants at the Bulungan Blok M Theater at 13.00 WIB. Participants are members of the Jakarta International Photo Festival (JIPFEST) photography community, which includes individuals with various levels of ability and photography educational backgrounds. This systematic approach is actively implemented by the JIPFEST community, a group of photography enthusiasts who regularly hold exhibitions, workshops, and mentoring sessions. The aim of this PKM is to equip participants with the ability to design photographic works with a strong message as well as develop appropriate concept elaborations. From training activities that provide a concrete approach to developing photographic works of art, including the steps in creating photographic works, it has proven to be effective as an important instrument in creating photographic works that not only convey a solid concept but also succeed in conveying a clear message. Both beginners and professional photographers can use these stages as a foundation for their creative process and improve their abilities in creating photography.